Risk of Malignant Neoplasm in Patients with Incident Rheumatoid Arthritis 1980–2007 in relation to a Comparator Cohort: A Population-Based Study. (17th August 2016) - Raheel, Shafay; Crowson, Cynthia S.; Wright, Kerry; Matteson, Eric L.
Abstract : Objective. To determine whether the incidence of malignancy is increased in patients with rheumatoid arthritis (RA) compared to a matched comparison cohort and to identify risk for any individual malignancy in RA. Methods. A cohort of 813 Olmsted County, Minnesota, residents who first fulfilled 1987 ACR criteria for RA in 1980–2007 was previously identified by medical record review. Medical records of 813 RA cases and a comparison cohort of age and sex matched Olmsted County residents without RA were evaluated retrospectively for cancer occurrence. Patients in both cohorts were followed until death, migration from Olmsted County, or 12/31/2014. Results. The RA and non-RA cohorts (mean age at incidence/index date: 55.9 [SD: 15.7] years; 68.4% females in both cohorts) were followed on average of 14.1 (SD: 7.7) and 14.9 (SD: 8.1) years, respectively. Prior to RA incidence/index date, 52 RA patients and 66 non-RA subjects had malignancies excluding NMSC (p = 0.21 ). During follow-up, significantly more malignancies occurred in patients with RA (n = 143 ) than in comparator subjects (n = 118 ; hazard ratio: 1.32; p = 0.027 ). Inclusion of NMSC obviated this difference. Conclusion. After excluding NMSC, there was a small to moderately increased risk of malignancies in patients with RA. Cancer surveillance is imperative in all patients with RA.